BOOK NOTICES / BOEKAANKONDIGINGS - Lategan, Bernard C. (Scriptura, 1985)
Ebeling, Gerhard 1985. The Truth of the Gospel: an exposition of Galatians. Philadelphia: Fortress Press.Knight, George A F 1984. Servant theology - A commentary on the book of Isaiah 40-55. Edinburgh: The Handsel Press.Martin-Archard, Robert & Re’emi, S Paul 1984. God’s people in crisis: Commentary on the book of Amos, and a commentary on the book of Lamentations. Grand Rapids, Michigan: Wm B Eerdmans.Knight, George A F 1984. Servant theology - A commentary on the book of Isaiah 56-66. Grand Rapids, Michigan: Wm B Eerdmans.Whittaker, Molly 1984. Jews and Christians: Graeco-Roman views. Cambridge: Cambridge University Press.Ogietree, Thomas W 1985. Hospitality to the stranger - Dimensions of moral understanding. Philadelphia: Fortress Press.Hazelton, Roger 1985. Graceful Courage - A venture in Christian humanism. Philadelphia: Fortress Press.Marity, Martin E 1984. Being good and doing good. Philadelphia: Fortress Press.Everett, William Johnson 1985. Blessed be the bond: Christian perspectives on marriage and family. Philadelphia: Fortress Press.Bruce, FF 1983. Israel and the nations. Great Britain: The Paternoster Press.Soggin, J Alberto 1984. A history of Israel: from the beginnings to the Bar Kochba revolt. A.D. SCM Press Ltd.Jennings, Theodore W Jr (ed) 1985. The vocation of the theologian. Philadelphia: Fortress Press.Reumann, John 1985. The supper of the Lord - The New Testament, ecumenical dialogues, and faith and order on eucharist. Philadelphia: Fortress Press.Rusch, William G 1985. Ecumenism - A movement toward church unity. Lux Verbi.Santmire, H Paul 1985. The travail of nature - The ambiguous ecological promise of Christian theology. Philadelphia: Fortress Press.Edwards, R A 1985. Matthew’s story of Jesus. Philadelphia: Fortress Press.Patte, Daniel 1948. Preaching Paul: Fortress resources for preaching. Philadelphia: Fortress Press.Mc Entire, C T & R R Wells (edd) 1984. History and historical understanding. Grand Rapids: Eerdmans.Diehl, Judith Ruhe 1985. A woman’s place - Equal partnership in daily ministry. Philadelphia: Fortress Press.Piediscalzi, Nicholas & Thobaben, Robert G 1985. Three worlds of Christian-marxist encounters. Philadelphia: Fortress Press.Himmelfarb, Martha 1983. Tours of hell - An apocalyptical form in Jewish and Christian literature. Philadelphia: Fortress Press.Smith, Gary Scott 1985. The seeds of secularization: Calvanism, culture, and pluralism in America, 1870-1915. Christian University Press, a subsidiary of Eerdmans.